Cone‑beam computed tomography analysis on root and canal morphology of mandibular first permanent molar among multiracial population in East Coast Malaysian population - Deng, Prunella Ubung; Halim, Mohamad Syahrizal; Masudi, Sam’an Malik; Al‑Shehadat, Saaid; Ahmad, Basaruddin (Medknow Publications, 2018)
Objective: The aim of this study is to investigate the variations in the number of root and canal in the mandibular first permanent molars (MFPMs) teeth in East Coast Malaysian population using cone‑beam computed tomography (CBCT). Materials and Methods: CBCT images which show MFPMs recorded in HUSM Dental Clinic between January 2015 and June 2016 was obtained and analyzed for their number of roots and canals. A total of 208 CBCT images of MFPMs were collected; 118 patients had unilateral molars and 90 patients had bilateral molars. The following observations were made: (1) root number; (2) number of canals per root; and (3) comparisons of number of roots and canals according to gender, ethnicity, and position. Results: The majority of cases of bilateral MFPM had the same number of roots (95.6%, 95% confidence interval [CI]: 89.01%, 98.78%) on both the right and left side and only 4 cases (4.4%, 95% CI: 1.22%, 10.99%) had 3 roots on the right and 2 roots on the left sides. The majority of cases had the same number of canals on both sides (66.7%, 95% CI: 55.95, 76.26%) and 33.3% (95% CI: 23.74%, 44.05%) with unequal number of canals. The occurrence of the number of canals was not independent of the sides of the arch (P < 0.001) and there was statistically significantly greater proportion of cases who had greater number of canals on the right side than the left (P = 0.03). The prevalence of right single‑rooted MFPM was very small at 0.3% (n = 1) in a Malay male (95% CI: 0.00, 1.83) and the most prevalent was two roots first molar (88.4%). The number of roots was not associated with sex or ethnic group (P > 0.05). The MFPM with a single root was found to have only one mesial canal.